Hubungan Asupan Makanan Dengan Status Gizi Pada Santri Pondok Pesantren Roudlatul Hidayah Desa Pakis Kecamatan Trowulan Kabupaten Mojokerto: Relationship between food intake and nutritional status in students of the Roudlatul Hidayah Islamic Boarding School, Pakis Village, Trowulan District, Mojokerto Regency - Khusniyati, Etik; Sari, Ayu Komala; Ro'ifah, Ifa (Universitas Muhammadiyah Sidoarjo, 2016)
The nutritional requirements change throughout life cycle, and closely related to growth and development of a person in his present life. Teenager Nutrition is one of the most important factors and major development determinants of teenager growth, as in adolescence, the hormonal changes that cause the rapid growth of other phases in life except the first year of life. This research aimed to investigate the relationship between dietary habit and students' nutritional status at boarding school of Roudlatul Hidayah . This research method used cross sectional analytic. The samples of research were all teenager students (15-17 years) in Roudlotul Hidayah Boarding School Pakis village District Trowulan Mojokerto in 2015 as many as 37 students, three people drop out because they could not be found during the research so that the sample 34 students. dietary food was measured by the Food Frequency Questionnaire and nutritional status of BMI calculation results. Data analysis used statistical test Spearman Rho. The results showed a total of 18 students (52.9%) had dietary habit in the category of less than statutes energy needs. The nutritional status of majority students were in the underweight category in 18 students (52.9%). Statistical data analysis with Spearman Rho test using SPSS version 20.0 was known that the P value (0.000) <α (0.01) so that there was a relationship between dietary habit and nutritional status. Meal frequency, type and amount of food would affect food intake that have an impact on nutritional status.